PSEN1 c.1292C<A Variant and Early-Onset Alzheimer’s Disease: A Scoping Review - Orozco-Barajas, Maribel; Oropeza-Ruvalcaba, Yulisa; Canales-Aguirre, Alejandro A.; Sánchez-González, Victor J. (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is the most common cause of dementia characterized by progressive loss of cognitive function with β-amyloid plaques and neurofibrillary tangles being its major pathologic findings. Whereas it is mainly a disease of the elderly, c. 5-10% of the cases are due to PSEN1, PSEN2 and APP mutations which are mostly associated with an Early Onset of the disease. The A413E (rs63750083) PSEN1 variant, identified in 2001, is associated with Early-Onset Alzheimer's Disease (EOAD). There is scant knowledge about the clinical manifestations and particular features of the disease. The aim of this scoping review is to synthesize the findings related with the A431E variant of PSEN1.The search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) statement, and the guideline proposed by Arksey and O'Malley. Analysis is performed using a narrative synthesis with a qualitative approach. A search of studies including the A431E variant of PSEN1, from 2001 to 2021, in five databases and one search engine, identified 247 studies. After removal of duplicates, 42 studies included the variant of interest were left. Given the conformation of the study samples, the results are divided in those carried out with participants who are carriers of the gene variant (seven studies), subjects with other PSEN variants (eleven studies) and with other variants associated with early-onset AD in PSEN1, PSEN2 and APP (24 studies). Results synthesis indicates most of the studies were conducted in Mexican and Mexican American participants in preclinical and clinical stages, only a minority of whom had only the variant of interest. The rest were made up of participants with a history of other PSEN and APP variants. The articles analyzed included carrier characteristics in categories such as genetics, clinical, imaging techniques, neuropsychology, neuropathology, and biomarkers. Family members' beliefs and caregivers' experiences were also included. Heterogeneity in both the studies found and carrier samples of EOAD-related gene variants does not allow for generalization of the findings. Future research should focus on reporting data on the progression of carrier characteristics through time.